Personality Effects on Romantic Relationship Quality through Friendship Quality: A Ten-Year Longitudinal Study in Youths - Yu, Rongqin (Public Library of Science, 2014)
This study examined whether individuals with different personality types (i.e., overcontrollers, undercontrollers, resilients) had different friendship quality development throughout adolescence. It also investigated whether personality types were indirectly related to romantic relationship quality in young adulthood, via friendship quality development in adolescence. The study employed six waves of longitudinal questionnaire data from Dutch youths who had a romantic relationship when they were young adults. Two age cohorts were followed, from 12 to 21 years and from 16 to 25 years, respectively. Findings showed that resilients reported higher mean levels of friendship quality during adolescence (i.e., more support from, less negative interaction with and less dominance from their best friend) than both overcontrollers and undercontrollers. Through the mean levels of friendship quality throughout adolescence, resilients indirectly experienced higher romantic relationship quality during young adulthood than both overcontrollers and undercontrollers. Thus, results provide support for a developmental model in which adolescent friendship quality is a mechanism linking personality types with young adulthood romantic relationship quality.